Preparation method of puncture-resistant aerogel heat-sealing film with self-repairing function

By constructing a double continuous interpenetrating network structure aerogel film through electrospinning and dynamic covalent bond self-healing technology, the contradiction between thermal insulation performance and mechanical properties of aerogel composite films under high filler content is resolved, and the puncture resistance and self-healing ability are improved, making it suitable for aerospace and new energy vehicle battery thermal management and other fields.

CN121471555APending Publication Date: 2026-02-06SHENZHEN XINFUYI INDAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511734482.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-24
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing aerogel composite films exhibit a contradiction between thermal insulation and mechanical properties at high filler contents, resulting in poor puncture resistance, brittle fracture, and inability to withstand harsh working conditions.

Method used

High-porosity nanofiber templates were prepared using electrospinning technology to generate silica aerogel networks in situ. These networks were then filled with dynamic covalent self-healing polymer networks to construct a bicontinuous interpenetrating network structure, which achieved self-healing function through the Diels-Alder reaction.

Benefits of technology

It achieves excellent puncture resistance and self-healing ability of aerogel films, improves the synergistic effect of thermal insulation and mechanical properties, and simplifies the convenience of engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121471555A_ABST
    Figure CN121471555A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material science and functional polymer materials, and particularly relates to a preparation method of a puncture-resistant aerogel heat-sealing film with a self-repairing function, which comprises the following steps: constructing a polyvinylpyrrolidone nanofiber sacrificial template through electrostatic spinning; generating a silicon dioxide aerogel network by an in-situ sol-gel method; removing the template through solvent extraction to obtain a continuous aerogel skeleton; introducing a furanized polyurethane and maleimide cross-linking agent precursor solution through vacuum infiltration; thermally initiating Diels-Alder reaction to form a dynamic covalent bond cross-linked polymer network; and finally carrying out hot-press molding. By the adoption of the technical scheme, collaborative optimization of heat insulation performance and mechanical performance can be achieved, the film is endowed with excellent puncture resistance and a heat triggering self-repairing function, and meanwhile the film has good heat sealing processability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials science and functional polymer materials technology, specifically a method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function. Background Technology

[0002] In cutting-edge fields such as aerospace and new energy vehicle battery thermal management, there is an urgent need for lightweight, flexible materials that combine ultra-low thermal conductivity with excellent mechanical properties. Silica aerogel, as a three-dimensional nanoporous network material, has a porosity exceeding 90% and a nanopore structure, which significantly restricts heat conduction between the gaseous and solid states. It possesses the lowest known thermal conductivity among solid materials and is a core potential thermal insulation material. However, pure aerogel, due to its porous and brittle framework, has low mechanical strength and poor toughness, making it difficult to process into practical films or fabrics, which severely restricts its engineering applications.

[0003] The current mainstream solution is an aerogel particle-polymer blending approach: aerogel particles are dispersed as fillers in polymer matrices such as polyurethane and silicone rubber, and composite films are prepared through processes such as coating and blade coating. This approach utilizes the flexibility and film-forming properties of the polymer to provide support for the aerogel, combining the thermal insulation and mechanical properties of both, thus solving the problem of aerogel molding. The resulting composite film has better thermal insulation performance than pure polymer films, meeting the flexible thermal insulation requirements at the time.

[0004] Existing solutions suffer from a fundamental bottleneck: there is an inherent contradiction between thermal insulation performance and mechanical properties. To achieve ultra-low thermal conductivity, the aerogel filler content needs to be increased to construct a continuous thermal resistance network. However, rigid aerogel particles with high filler content will disrupt the continuity of the polymer matrix, destroying the polymer chain entanglement and stress transfer network. Under external force, stress concentrates at the particle-matrix interface, easily initiating and propagating microcracks, resulting in poor puncture resistance and brittle fracture of the film. Furthermore, the thermal bridges formed by the damage are irreversible, making it unsuitable for the harsh working conditions of thermal and mechanical coupling. This has become a key obstacle restricting the performance upgrade of aerogel composite films.

[0005] Therefore, the present invention provides a method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function. Summary of the Invention

[0006] In order to overcome the shortcomings of the prior art, at least one technical problem raised in the background art is solved.

[0007] The technical solution adopted by this invention to solve its technical problem is as follows: A method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function, comprising the following process steps: Step 1: Preparation of a polymeric nanofiber sacrificial template. Using electrospinning technology, a sacrificial polymer that is completely soluble in a specific solvent is used to prepare a nanofiber membrane with high porosity and a three-dimensional interconnected network structure. The sacrificial polymer is polyvinylpyrrolidone (PVP), with a weight-average molecular weight of 1,300,000 g / mol. The PVP is dissolved in a binary mixed solvent composed of N,N-dimethylformamide (DMF) and anhydrous ethanol, wherein the mass ratio of DMF to anhydrous ethanol is 7:3, to prepare a 12% (w / w) spinning precursor solution. The equipment parameters for the electrospinning process were set as follows: a 22-gauge stainless steel spinneret with an inner diameter of 0.41 mm was used; the precursor solution was ejected at a constant rate of 0.5 mL / h via a micro-injection pump; an 18 kV DC high voltage was applied between the spinneret and the receiving device; the linear distance between the spinneret tip and the receiving device was set to 20 cm; the receiving device was a grounded rotating roller with a diameter of 15 cm and an aluminum foil-covered surface, with a rotation speed set to 200 rpm. The entire spinning process was carried out under controlled conditions of an ambient temperature of 25°C and a relative humidity of 40%. Through the above process, a macroscopically uniform, randomly oriented polyvinylpyrrolidone nanofiber sacrificial template membrane with an average fiber diameter of 300 nm and a porosity of not less than 85% was prepared.

[0008] Step 2: In-situ generation of silica aerogel network. The nanofiber sacrificial template membrane obtained in Step 1 is completely immersed in a pre-prepared silica sol-gel precursor solution. Through subsequent gelation, solvent replacement and supercritical drying processes, a continuous and complete silica wet gel network is constructed in-situ in the gaps between the fiber networks of the sacrificial template, and finally transformed into a dry gel, i.e., aerogel. The preparation process of the silica sol-gel system precursor solution is as follows: using tetraethyl orthosilicate (TEOS) as the silicon source, anhydrous ethanol as the solvent, deionized water as the hydrolysis agent, and hydrochloric acid as the acid catalyst. The molar ratio of each component is precisely controlled as TEOS: anhydrous ethanol: deionized water: hydrochloric acid = 1:25:4:0.001. Specifically, in the preparation, TEOS is first mixed with half the volume of anhydrous ethanol, denoted as solution A; then deionized water, hydrochloric acid, and the remaining half volume of anhydrous ethanol are mixed, denoted as solution B. Under magnetic stirring at 300 rpm, solution B was added dropwise to solution A, and the reaction was continued in a constant temperature water bath at 25 degrees Celsius for 60 minutes to complete the hydrolysis and preliminary condensation reaction of TEOS and obtain a clear and transparent precursor solution. Subsequently, the sacrificial template membrane was placed in the precursor solution and impregnated under a vacuum of 1 kPa for 2 hours to ensure that the sol completely and without bubbles penetrated into all the pores inside the template. After penetration, a 28% (w / w) ammonia solution was added to the system as an alkaline catalyst, at a rate of 0.1 mL of ammonia per 100 mL of precursor solution, to rapidly initiate gelation of the system. The impregnated template membrane, along with the solution, was sealed and aged in a constant temperature oven at 45-62°C, preferably 50°C, for 48 hours to form a gel block composed of silica wet gel and PVP fiber. After aging, the composite gel block was transferred to pure anhydrous ethanol for solvent replacement, with fresh anhydrous ethanol replaced every 12 hours for a total of 5 replacements, in order to thoroughly remove moisture, residual catalyst, and reaction byproducts from the gel pores. Finally, the solvent-displaced composite gel block was placed in a high-pressure supercritical fluid drying device, using liquid carbon dioxide as the drying medium. The drying process is set as follows: First, the temperature inside the device is raised to 40 degrees Celsius, and the pressure is increased to 10 MPa. Under these conditions, the sample is continuously rinsed with liquid carbon dioxide for 8 hours. Then, while keeping the temperature constant, the pressure was slowly released to atmospheric pressure at a constant rate of 0.2 MPa / min, thereby removing the ethanol in the pores without damaging the nanoporous structure, and obtaining a silica aerogel / PVP fiber composite material.

[0009] Step 3: Removal of the sacrificial template and acquisition of the continuous aerogel framework. Utilizing the good solubility of PVP in a specific solvent and the chemical inertness of the silica framework, the PVP nanofiber component in the composite material is selectively removed by solvent extraction, thereby exposing a three-dimensional, continuous, macroscopically self-supporting pure silica aerogel framework composed of silica, which is the opposite of the sacrificial template network structure. In practice, the silica aerogel / PVP fiber composite material obtained in step two is placed in the extraction chamber of a Soxhlet extractor, using anhydrous ethanol as the extraction solvent. Continuous extraction is performed for 24 hours at the boiling point of anhydrous ethanol (approximately 78 degrees Celsius). Through repeated solvent circulation and condensation, the PVP component is completely dissolved and carried out of the composite material system. After extraction, the obtained pure silica aerogel skeleton is dried in a vacuum oven at 80 degrees Celsius for 12 hours to completely remove residual ethanol, obtaining the final monolithic silica aerogel skeleton with a high specific surface area and highly interconnected pore structure for subsequent steps.

[0010] Step four involves the construction and filling of a dynamic covalently bonded self-healing polymer network. The core of this step is the synthesis of a prepolymer with a flexible main chain and reversible covalent functional groups. This prepolymer is then infiltrated into the pores of the silica aerogel framework obtained in step three. Finally, thermally initiated polymerization crosslinking forms a continuous polymer network with thermally reversible repair capabilities, filling the pores of the aerogel. This self-healing polymer system is based on the chemical principle of the Diels-Alder (DA) reaction.

[0011] Furthermore, the specific construction process of the dynamic covalent self-healing polymer network is as follows: First, a linear thermoplastic polyurethane (f-TPU) prepolymer with furan functional groups was synthesized. The process involved reacting polytetrahydrofuran glycol (PTMEG, number-average molecular weight 2000 g / mol), 4,4'-methylene bis(phenyl isocyanate) (MDI), and 1,4-butanediol (BDO) in a molar ratio of 1:3:2 as chain extenders in 1,2-dichloroethane solvent at 80°C for 6 hours using dibutyltin dilaurate as a catalyst to synthesize the isocyanate-terminated polyurethane prepolymer. Subsequently, the reaction system was cooled to 60 degrees Celsius, and a stoichiometric excess of furfurylamine was added. This allowed the amino groups of furfurylamine to react with the remaining isocyanate groups on the polyurethane chains, thereby bonding furan functional groups to the polyurethane molecular chains. After the reaction continued for 4 hours, the product was precipitated in methanol, filtered, washed, and vacuum dried to obtain furan-functionalized thermoplastic polyurethane (f-TPU). The degree of furan functionalization was controlled by 1H NMR spectroscopy, which determined that each polymer chain contained an average of 2.5 furan groups. Next, a precursor solution was prepared. The synthesized f-TPU was used as the polymer matrix containing dienes, and 1,3,5-tris(maleimide methyl)benzene was selected as a trifunctional dienophilic crosslinking agent. The f-TPU and this crosslinking agent were dissolved together in tetrahydrofuran (THF) solvent to prepare a homogeneous, transparent solution with a total solids content of 15% (mass fraction), ensuring a precise 1:1 molar ratio of furan groups to maleimide groups. Next, vacuum-assisted infiltration was performed. The pure silica aerogel framework obtained in step three was completely immersed in the above-mentioned precursor filling solution and kept in a vacuum environment of 1 kPa for 4 hours. The polymer solution was thoroughly and uniformly drawn into all the nanopores of the aerogel framework using negative pressure. Then, the solvent is removed and thermosetting is performed. The fully permeated composite is removed from the solution and slowly dried in a vacuum oven at 40°C for 24 hours to completely remove the THF solvent. After solvent removal, the composite is placed in a glove box or oven under an inert atmosphere filled with nitrogen, and the temperature is programmed to rise to 80°C and held for 6 hours. At this temperature, the furan groups on the f-TPU molecular chain undergo a DA cycloaddition reaction with the maleimide groups on the crosslinking agent molecules, forming stable covalent crosslinking points, thereby forming a three-dimensional continuous, chemically crosslinked polyurethane elastomer network in situ within the pores of the silica aerogel framework.

[0012] Step 5: Final treatment and hot pressing of the film. The double continuous interpenetrating network composite material obtained in Step 4 is placed between two polyimide release films and placed in a flatbed hot press. Hot pressing is performed at 130°C and 1 MPa for 5 minutes. This temperature is higher than the dissociation temperature of the DA adduct (reverse-DA reaction temperature, typically 110–120°C), causing some DA bonds to temporarily break, imparting a certain degree of fluidity to the polymer network, which helps eliminate internal micro-defects and makes the film surface smoother and denser. After the pressure is removed and the film is cooled to room temperature, the DA bonds reform, and the network structure is restored. This step not only completes the final shaping of the film but also verifies and imparts its heat-sealing properties.

[0013] Through the aforementioned series of precisely controlled steps, the final product is a puncture-resistant aerogel heat-sealing film with self-healing capabilities. Its microstructure consists of: a continuous porous framework with pore sizes on the order of 50 nanometers, formed by the fusion of nano-silica particles, serving as the first continuous phase and providing thermal insulation; and a seamless polymer network, formed by dynamically covalently cross-linked polyurethane elastomer completely filling the pores of the framework, serving as the second continuous phase and providing mechanical support, puncture resistance, and self-healing functions.

[0014] The beneficial effects of this invention are reflected in: By constructing a double continuous interpenetrating network structure, this invention fundamentally solves the contradiction between the interfacial incompatibility between the thermal insulation filler and the polymer matrix, as well as the mutual constraint between mechanical and thermal properties, in traditional physical blends. The continuous aerogel skeleton ensures extremely low heat conduction paths, while the continuous polymer network ensures excellent stress transfer and energy dissipation capabilities, achieving a synergistic improvement in both properties. Third, the prepared film exhibits excellent puncture resistance. When the film is subjected to a sharp object, the continuous, highly tough cross-linked polyurethane network can effectively blunt the crack tip and absorb and dissipate puncture energy through a wide range of plastic deformation, significantly improving the material's puncture resistance and avoiding the brittle fracture behavior of traditional aerogel composites. When the film suffers macroscopic damage from punctures or scratches, simply heating the damaged area to above 120 degrees Celsius triggers the reverse reaction of DA addition bonds in the polymer network. This breaks the crosslinking points, restores the mobility of the polymer chains, and allows them to automatically fill and heal the damaged area under the influence of surface tension and molecular chain diffusion. Subsequently, when the temperature drops below 80 degrees Celsius, the DA reaction resumes, and covalent bonds are reformed at the damaged interface, thus restoring the material's structural integrity and mechanical properties. Simultaneously, it seals the thermal bridges caused by the damage, restoring its thermal insulation performance. The self-healing chemical system (DA reaction) is thermally reversible, giving the final film material excellent thermoplastic processability, especially heat-sealing performance. This greatly simplifies the cutting, splicing, and integration processes of the film in practical applications, allowing for easy sealing with other components via hot pressing, thus improving the convenience of engineering applications. The continuous aerogel framework prepared by in-situ generation combined with template method has higher structural integrity and more effective thermal resistance network compared with particulate filling system. It also forms a physical interlocking structure with the subsequently filled polymer network, with strong interfacial bonding force, avoiding the failure mode of filler debonding from matrix under high strain. Attached Figure Description

[0015] The invention will now be further described with reference to the accompanying drawings.

[0016] Figure 1 This is a schematic flowchart of a method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function according to the present invention.

[0017] Figure 2 This is a schematic diagram of the microscopic double continuous interpenetrating network structure of the heat-sealing film described in this invention; Figure 3 This is a schematic diagram of the self-healing process of the heat-sealing film described in this invention. Detailed Implementation

[0018] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below in conjunction with specific embodiments.

[0019] like Figure 1-3 As shown in the embodiment of the present invention, a method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function includes the preparation of a polymer nanofiber sacrificial template as the first key step. The purpose of this step is to construct a temporary framework with a three-dimensional interconnected network structure and high porosity. The morphology of this framework will directly determine the macroscopic morphology and pore structure of the subsequently generated silica aerogel network. In some embodiments, the selected sacrificial polymer is polyvinylpyrrolidone (PVP), whose weight-average molecular weight is precisely controlled at 1,300,000 g / mol. The higher molecular weight is beneficial for forming a continuous and stable jet during electrospinning, thereby obtaining high-quality nanofibers. To prepare the spinning precursor solution, the polyvinylpyrrolidone was first dissolved in a binary mixed solvent. This mixed solvent consisted of N,N-dimethylformamide (DMF) and anhydrous ethanol, with a strictly controlled mass ratio of 7:3. This solvent ratio was optimized to adjust the solution's conductivity, surface tension, and evaporation rate to obtain nanofibers with uniform morphology. A final spinning precursor solution with a mass fraction of 12% was prepared. This concentration ensured that the solution had a suitable viscosity to avoid droplet ejection or fiber interruption during spinning.

[0020] Subsequently, the precursor solution was prepared into a nanofiber membrane using electrospinning technology. Specifically, the process parameters were set as follows: the precursor solution was loaded into a syringe and smoothly ejected at a constant rate of 0.5 ml / h through a 22-gauge stainless steel spinneret with an inner diameter of 0.41 mm using a micro-injection pump. A DC high voltage of up to 18 kV was applied between the spinneret and the receiving device; this strong electric field was crucial for driving the Taylor cone formation and the stretching and thinning of the polymer jet. The straight-line distance between the spinneret tip and the receiving device, i.e., the spinning distance, was set to 20 cm. This distance ensured sufficient time for the solvent to evaporate before the fibers reached the receiving device, while avoiding excessive attenuation of the electric field strength. For example, the receiving device uses a grounded rotating roller with a diameter of 15 cm, whose surface is pre-covered with conductive aluminum foil, and its rotation speed is set to 200 rpm. The rotating collection method helps to obtain a more macroscopically uniform nonwoven fabric structure with randomly oriented fibers. The entire electrospinning process is carried out in a chamber with controlled environmental parameters, with the ambient temperature maintained at 25 degrees Celsius and the relative humidity controlled at 40%. Stable environmental conditions are an important prerequisite for ensuring the repeatability of fiber morphology and diameter. According to the above-described scheme provided in the embodiments of the present invention, a macroscopically uniform, loosely structured polyvinylpyrrolidone nanofiber sacrificial template membrane with randomly oriented fibers is finally prepared. Characterization by scanning electron microscopy shows that the average fiber diameter of the template membrane is approximately 300 nanometers, and its calculated porosity is no less than 85%. This high porosity and three-dimensional connectivity lay a crucial structural foundation for the subsequent complete penetration of the sol and the formation of a continuous aerogel network.

[0021] Based on this, in-situ generation of silica aerogel networks is carried out. The goal of this step is to introduce the silica sol-gel system precursor solution into the pores of the sacrificial template, and through a series of subsequent chemical and physical processes, construct a continuous and complete silica wet-gel network that is the opposite phase to the template network in the gaps of the template fiber network, and finally transform it into a porous aerogel through supercritical drying; Specifically, the precursor solution of the silica sol-gel system needs to be prepared first. This system uses tetraethyl orthosilicate (TEOS) as the silicon source, anhydrous ethanol as the co-solvent to ensure that the silicon source and water are miscible, deionized water as the necessary reagent for the hydrolysis reaction, and hydrochloric acid as the acidic catalyst to promote the hydrolysis reaction and inhibit the excessively rapid occurrence of the polycondensation reaction. To obtain a uniform gel network, the molar ratio of each component is precisely controlled, and the ratio is as follows: TEOS: Anhydrous ethanol: Deionized water: Hydrochloric acid = 1:25:4:0.001; This ratio ensures complete hydrolysis of TEOS and a smooth subsequent gelation process. In the specific preparation process, to avoid adverse hydrolysis caused by uneven local concentrations, TEOS is first mixed with half the total amount of anhydrous ethanol, denoted as solution A; then deionized water, hydrochloric acid, and the remaining half of the anhydrous ethanol are mixed, denoted as solution B. Under magnetic stirring at 300 rpm, solution B was slowly added dropwise to solution A using a dropper. The entire mixing process was carried out in a constant-temperature water bath at 25 degrees Celsius and the reaction was continued for 60 minutes. This process completed the hydrolysis of TEOS molecules and the initial linear condensation reaction, ultimately yielding a clear, transparent sol precursor solution that can be stored stably for a period of time.

[0022] Subsequently, the PVP nanofiber sacrificial template membrane obtained in step one was completely immersed in the aforementioned precursor solution. To ensure that the sol could completely and without bubbles penetrate into all the tiny pores inside the template, the entire impregnation system was placed in a vacuum drying oven and subjected to vacuum-assisted infiltration treatment at an absolute pressure of 1 kPa for 2 hours. After infiltration, a 28% (w / w) ammonia solution is added to the system as an alkaline catalyst, with the addition amount controlled at 0.1 mL of ammonia per 100 mL of precursor solution. The addition of ammonia rapidly increases the pH of the system, thereby greatly accelerating the polycondensation reaction rate and initiating a macroscopic sol-to-gel transformation. The catalyst-impregnated template membrane, along with the solution, is transferred to a sealed container and aged in a constant temperature incubator at 45-65°C, preferably 50°C, for 48 hours. The aging process aims to enhance the strength of the gel network, enabling it to withstand the stresses of subsequent processing. After aging, a gel block composed of silica wet gel and PVP fiber network is obtained. To remove residual moisture, unreacted monomers, catalysts, and reaction byproducts (mainly ethanol) from the gel pores, a thorough solvent replacement is required. The composite gel block is transferred to a container filled with pure anhydrous ethanol, and fresh anhydrous ethanol is added every 12 hours for a total of 5 replacements to ensure that the solvent in the pores is completely replaced by ethanol. Finally, supercritical fluid drying technology was used to remove ethanol from the pores, thus avoiding the collapse of the gel network structure caused by the huge capillary forces during conventional evaporation drying. The solvent-displaced composite gel block was placed in a high-pressure supercritical fluid drying device, using liquid carbon dioxide as the drying medium. In some embodiments, the drying process is precisely set as follows: first, the temperature inside the apparatus is raised to 40 degrees Celsius, while the pressure is increased to 10 MPa (above the critical point of carbon dioxide: 31.1 degrees Celsius, 7.38 MPa). Under this supercritical state, the sample is continuously flushed with carbon dioxide fluid for 8 hours to extract ethanol from the pores. Then, while maintaining a constant temperature of 40 degrees Celsius, the system pressure is slowly released to atmospheric pressure at a constant rate of 0.2 MPa / min. During this process, carbon dioxide directly transforms from a supercritical state to a gaseous state and escapes, thus completing the drying process without damaging the nanoporous structure, obtaining a silica aerogel / PVP fiber composite material.

[0023] The next step is the removal of the sacrificial template and the acquisition of a continuous aerogel framework. This step utilizes the good solubility of PVP in a specific solvent and the chemical inertness of the silica framework to selectively remove the PVP nanofiber component from the composite material via solvent extraction. This exposes a three-dimensional, continuous, macroscopically self-supporting pure silica aerogel framework composed of silica, whose network structure is the opposite of the original sacrificial template network structure. In one example, the silica aerogel / PVP fiber composite material obtained in step two was placed in the extraction chamber of a Soxhlet extractor, using anhydrous ethanol as the extraction solvent. Continuous extraction was performed at the atmospheric boiling point of anhydrous ethanol (approximately 78 degrees Celsius) for 24 hours. In the Soxhlet extractor, heated ethanol vapor rose and was condensed. The condensed pure ethanol droplets were then dripped into the extraction chamber to soak the sample. When the liquid level reached the highest point of the siphon tube, the ethanol solution containing dissolved PVP was siphoned back into the flask, thus completing one extraction cycle. Through this repeated circulation and condensation of the solvent, the PVP component was continuously and efficiently dissolved and carried out of the composite material system. After the extraction process is completed, the obtained pure silica aerogel skeleton is removed from the extractor and placed in a vacuum oven at 80 degrees Celsius for 12 hours to dry completely remove the residual extraction solvent ethanol from the skeleton pores. Thus, a monolithic silica aerogel framework with extremely high specific surface area and highly interconnected pore structure was obtained for subsequent polymer network filling.

[0024] To construct a polymer network with both mechanical support and self-healing capabilities, it is necessary to construct and fill a dynamic covalent self-healing polymer network. The core of this step lies in synthesizing a prepolymer with a flexible main chain and reversible covalent functional groups on its side chains or end groups. This prepolymer is then infiltrated into the pores of the silica aerogel framework obtained in the previous step. Finally, thermally initiated polymerization crosslinking forms a continuous polymer network with thermally reversible repair capabilities in situ within the aerogel pores. The self-healing polymer system used in this invention is based on the classic Diels-Alder (DA) reaction. This reaction can undergo cycloaddition under relatively mild conditions (e.g., 80°C) to form stable covalent bonds, while at higher temperatures (e.g., 120°C), a reverse DA reaction occurs, causing the covalent bonds to break. This thermal reversibility is the chemical basis for achieving the material's self-healing and heat-sealing properties.

[0025] Further, the specific construction process of the dynamic covalent self-healing polymer network is as follows: First, a linear thermoplastic polyurethane (f-TPU) prepolymer with furan functional groups needs to be synthesized, wherein the furan groups serve as dienes in the DA reaction. This synthesis process is carried out under strict nitrogen protection to prevent the isocyanate groups from reacting with moisture in the air. Polytetrahydrofuran glycol (PTMEG, with a number-average molecular weight of 2000 g / mol, as the flexible soft segment), 4,4'-methylenebis(phenyl isocyanate) (MDI, as the hard segment), and 1,4-butanediol (BDO, as the chain extender) in a molar ratio of 1:3:2 are dissolved in 1,2-dichloroethane solvent, and dibutyltin dilaurate is added as a catalyst. The reaction system is heated to 80 degrees Celsius and reacted for 6 hours; this step synthesizes a polyurethane prepolymer with isocyanate end groups. Subsequently, the temperature of the reaction system is lowered to 60 degrees Celsius, and a stoichiometric excess of furfurylamine is added. The primary amino groups on furfurylamine molecules can react efficiently with the remaining isocyanate groups on the polyurethane chains, thereby covalently bonding furan ring-containing functional groups to the ends or side chains of the polyurethane molecular chains. After this functionalization reaction lasted for 4 hours, the reaction product was poured into a large amount of methanol for precipitation. Through filtration, repeated washing with methanol, and final vacuum drying, pure furan-functionalized thermoplastic polyurethane (f-TPU) powder was obtained. The product structure was characterized by ¹H NMR spectroscopy, and the reactant ratio was precisely controlled to ensure that each polymer chain in the final product contained an average of 2.5 furan groups, guaranteeing the formation of subsequent cross-linking networks.

[0026] Next, a polymer precursor solution for filling was prepared. The synthesized f-TPU was used as the diene-containing polymer matrix, and 1,3,5-tris(maleimide methyl)benzene was selected as a trifunctional dienophilic crosslinking agent. f-TPU and the crosslinking agent were weighed in a precise 1:1 molar ratio to ensure a furan group to maleimide group, and dissolved together in tetrahydrofuran (THF) solvent to prepare a homogeneous, transparent solution with a total solids content of 15% (mass fraction). This precise stoichiometry is crucial to ensuring the formation of a perfect crosslinked network in the subsequent DA reaction and preventing residual functional groups from affecting material properties.

[0027] Next, vacuum-assisted infiltration is performed. The pure olica aerogel framework obtained in step three is completely immersed in the prepared precursor solution, and the entire system is placed in a vacuum environment of 1 kPa for 4 hours. The negative pressure effectively removes air from the nanopores of the aerogel framework, allowing the viscous polymer solution to be thoroughly and uniformly drawn into all the internal pores of the aerogel framework until saturation.

[0028] Next, solvent removal and network thermosetting are performed. The fully permeated composite is removed from the solution and placed in a vacuum oven at 40°C for slow drying for 24 hours. The lower temperature and vacuum environment help to remove the solvent THF gently, avoiding uneven polymer distribution or defects in the pores due to rapid solvent evaporation. After the solvent is completely removed, the dry composite is placed in a glove box or oven protected by an inert atmosphere filled with nitrogen and heated to 80°C using a programmed temperature rise method, and held at this temperature for 6 hours. Under these temperature and time conditions, the furan groups on the f-TPU molecular chain undergo a DA cycloaddition reaction with the maleimide groups on the crosslinking agent molecules, forming stable covalent crosslinking points, thereby in-situ polymerization within the pores of the silica aerogel framework to form a three-dimensional continuous, chemically crosslinked polyurethane elastomer network. The resulting microscopic bicontinuous interpenetrating network structure is shown in the attached figure. Figure 2 As shown, the continuous porous silica aerogelatinized GEO skeleton and the dynamically covalently cross-linked polyurethane elastomer network interpenetrate each other, forming a physically interlocked structure.

[0029] Finally, the film undergoes final treatment and hot pressing. The bicontinuous interpenetrating network composite material obtained in step four is sandwiched between two polyimide release films to prevent it from sticking to the hot press plate, and then placed in a flatbed hot press. Hot pressing is performed at 130°C and 1 MPa for 5 minutes. The chosen 130°C is higher than the dissociation temperature of the DA adduct (i.e., the reverse-DA reaction temperature, typically in the range of 110–120°C). At this temperature, some DA crosslinks temporarily undergo reversible breakage, giving the crosslinked polymer network a certain degree of macroscopic fluidity. The applied pressure helps eliminate any microscopic defects that may exist within the material and makes the film surface smoother and denser. After the pressure is removed and the film is cooled to room temperature, the temperature drops to the range where the DA reaction occurs, and the broken DA bonds reform, allowing the network structure to spontaneously recover. This step not only completes the final shaping of the film, giving it a regular thickness and a smooth surface, but also verifies and endows the material with excellent heat-sealing properties from a process perspective.

[0030] Through the above series of precisely controlled steps, the final product obtained is the puncture-resistant aerogel heat-sealing film with self-healing function described in this invention. Its microstructure features are as follows: a continuous porous framework with pore sizes at the 50-nanometer level, formed by the fusion of nano-silica particles through the neck, serves as the first continuous phase. Due to its inherent nanoporous structure and tortuous heat transfer path, this phase undertakes the main thermal insulation function; and a polymer network without any interruptions, formed by a polyurethane elastomer based on DA reaction dynamically covalently cross-linked, forms the second continuous phase. Due to the flexibility of its polymer chains and the integrity of the cross-linked network, this phase provides macroscopic mechanical support, puncture resistance, and self-healing function under external heating field excitation. Appendix Figure 3 The diagram illustrates the self-healing process of the heat-sealing film. When a damaged area appears on the film surface, the polymer network undergoes decrosslinking and flow through local heating, thereby healing the damage. After cooling, it recrosslinks and restores structural integrity.

[0031] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function, characterized in that, Includes the following steps: Step 1: Preparation of polymer nanofiber sacrificial template; Step 2: In-situ generation of silica aerogel network. Inside the three-dimensional interconnected network structure of the sacrificial template, a silica wet gel network is constructed in-situ through a sol-gel process, followed by supercritical fluid drying to form a silica aerogel / sacrificial template composite material. Step 3: Removal of the sacrificial template and acquisition of a continuous aerogel skeleton. The polymer nanofiber sacrificial template in the composite material is selectively removed by solvent extraction to obtain a macroscopically self-supporting pure silica aerogel skeleton with a three-dimensional continuous interconnected pore structure. Step 4: Construction and filling of the dynamic covalent self-healing polymer network. A precursor solution containing a prepolymer with thermally reversible dynamic covalent functional groups and a matching crosslinking agent is prepared, and the precursor solution is completely permeated into the through pores of the pure silica aerogel skeleton. Inside the pores of the pure silica aerogel skeleton, a reversible covalent bond formation reaction is initiated by heat between the prepolymer and the crosslinking agent, thereby constructing a three-dimensional continuous dynamic covalent crosslinked polymer network that permeates the silica aerogel skeleton in situ. Step 5: Final treatment and hot pressing of the film. The double continuous interpenetrating network composite material obtained in Step 4 is placed between two polyimide release films and placed in a flatbed hot press for hot pressing. Then it is cooled to room temperature to complete the final shaping of the film and give it heat-sealing properties.

2. The method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function according to claim 1, characterized in that, In step one, the specific steps for preparing the polymer nanofiber sacrificial template are as follows: using electrospinning technology, a spinning precursor solution of a sacrificial polymer that can be completely dissolved in a specific solvent is prepared into a nanofiber membrane with high porosity and a three-dimensional interconnected network structure by electrospinning equipment, so as to serve as the polymer nanofiber sacrificial template.

3. The method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function according to claim 2, characterized in that, The sacrificial polymer is polyvinylpyrrolidone; the spinning precursor solution is prepared by dissolving the polyvinylpyrrolidone in a binary mixed solvent composed of N,N-dimethylformamide and anhydrous ethanol, wherein the mass ratio of N,N-dimethylformamide to anhydrous ethanol is 7:3, and the mass fraction of the polyvinylpyrrolidone in the spinning precursor solution is 12%.

4. The method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function according to claim 3, characterized in that, The process parameters for the electrospinning technology are set as follows: a spinneret with an inner diameter of 0.41 mm is used, and the precursor solution is fed out at a constant rate of 0.5 ml / h; a DC high voltage of 18 kV is applied between the spinneret and the receiving device; the straight-line distance between the tip of the spinneret and the receiving device is set to 20 cm; the receiving device is a grounded rotating roller with an aluminum foil surface and a rotation speed of 200 rpm; and the entire electrospinning process is carried out under controlled conditions with an ambient temperature of 25 degrees Celsius and a relative humidity of 40%.

5. The method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function according to claim 1, characterized in that, In step two, the specific steps for constructing the in-situ silica wet gel network include: A precursor solution for a silica sol-gel system was prepared, using tetraethyl orthosilicate as the silicon source, anhydrous ethanol as the solvent, deionized water as the hydrolysis agent, and hydrochloric acid as the acid catalyst. The sacrificial template is completely immersed in the precursor solution, and vacuum-assisted permeation is used to ensure that the precursor solution completely fills the internal pores of the template. An aqueous ammonia solution, which acts as an alkaline catalyst, is added to the system to initiate gelation. The impregnated template is then sealed together with the solution and aged at a constant temperature of 45-65 degrees Celsius to form a gel block composed of silica wet gel and sacrificial template fibers. The composite gel block was subjected to solvent replacement to completely remove moisture, residual catalyst, and reaction byproducts from the gel pores.

6. The method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function according to claim 5, characterized in that, In the precursor solution of the silica sol-gel system, the molar ratio of each component is: Ethyl orthosilicate: anhydrous ethanol: deionized water: hydrochloric acid = 1:25:4:0.001; The vacuum-assisted permeation was carried out for 2 hours under a vacuum of 1 kPa; the ammonia solution had a mass fraction of 28%, and was added at a rate of 0.1 ml per 100 ml of precursor solution; the aging process lasted for 48 hours; the solvent replacement used pure anhydrous ethanol as the replacement solvent, and was replaced every 12 hours for a total of 5 replacements; the supercritical fluid drying process used liquid carbon dioxide as the drying medium, and was carried out under conditions of 40 degrees Celsius and 10 MPa, and then the temperature was kept constant, and the pressure was slowly released to atmospheric pressure at a rate of 0.2 MPa / min.

7. The method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function according to claim 1, characterized in that, In step four, the thermally reversible dynamic covalent bond is based on the chemical principles of the Diels-Alder reaction and the reverse Diels-Alder reaction; the prepolymer with thermally reversible dynamic covalent functional groups is a linear polymer with furan functional groups on its side chains or end groups, which acts as a diene in the Diels-Alder reaction; the crosslinking agent is a multifunctional molecule with maleimide functional groups, which acts as a dieophile in the Diels-Alder reaction.

8. The method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function according to claim 7, characterized in that, The linear polymer with furan functional groups is a furan-functionalized thermoplastic polyurethane, and its synthesis method includes the following steps: Under nitrogen protection, polytetrahydrofuran glycol, 4,4'-methylenebis(phenyl isocyanate) and 1,4-butanediol in a molar ratio of 1:3:2 were reacted in 1,2-dichloroethane solvent with dibutyltin dilaurate as catalyst at 80 degrees Celsius to synthesize a polyurethane prepolymer with terminal isocyanate groups. The reaction system is cooled to 60 degrees Celsius, and an excess of stoichiometric furfurylamine is added. The amino groups of furfurylamine react with the remaining isocyanate groups on the polyurethane chain, thereby bonding the furan functional group to the polyurethane molecular chain to obtain the furan-functionalized thermoplastic polyurethane.

9. The method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function according to claim 7, characterized in that, In step four, the crosslinking agent is 1,3,5-tris(maleimide methyl)benzene; The precursor solution is prepared by dissolving the furan-functionalized thermoplastic polyurethane and the 1,3,5-tris(maleimide methyl)benzene in tetrahydrofuran solvent, ensuring a molar ratio of furan groups to maleimide groups of 1:1, to prepare a solution with a total solid content of 15% by mass. The permeation process involves immersing a pure silica aerogel skeleton in the precursor solution and maintaining it in a vacuum environment of 1 kPa for 4 hours.

10. The method for preparing a puncture-resistant aerogel heat-sealing film with self-healing function according to claim 9, characterized in that, In step five, before initiating the reversible covalent bond formation reaction, the fully permeated complex is dried in a vacuum oven at 40 degrees Celsius for 24 hours to completely remove the tetrahydrofuran solvent; the thermal initiation reaction is carried out in an inert atmosphere filled with nitrogen at 80 degrees Celsius for 6 hours.